Urease Functionalized Silica: A Biohybrid Substrate To Drive Self-Mineralization - Ortega, Ilida (2008)
The present work explores the enzymatic driven biomineralization of a model silica substrate. Jack Bean Urease was covalently anchored onto synthetic aminopropyl-capped silica spheres. After several hours of aging at physiological temperatures in the presence of urea, Ca(II) and phosphate ions, homogeneous nanoparticulated hydroxyapatite-like shells were obtained.